2019
DOI: 10.1534/g3.118.200831
|View full text |Cite
|
Sign up to set email alerts
|

SNZ3 Encodes a PLP Synthase Involved in Thiamine Synthesis in Saccharomyces cerevisiae

Abstract: Pyridoxal 5′-phosphate (the active form of vitamin B 6 ) is a cofactor that is important for a broad number of biochemical reactions and is essential for all forms of life. Organisms that can synthesize pyridoxal 5′-phosphate use either the deoxyxylulose phosphate-dependent or -independent pathway, the latter is encoded by a two-component pyridoxal 5′-phosphate synthase. Saccharomyces cerevisiae contains three paralogs of the two-component SNZ/SNO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 55 publications
3
14
0
Order By: Relevance
“…In contrast to the SNZ1/SNO1 gene pair, which is located in the middle of the right arm of CHRXIII, SNZ2 / SNO2 and SNZ3 / SNO3 are found in subtelomeric regions of CHRXIV and VI, respectively, and are flanked by the thiamine biosynthetic genes THI12 and THI5 , respectively. Their increased expression upon thiamine depletion is consistent with the role of PLP in thiamine biosynthesis (Paxhia & Downs, ). The demonstration that Snz proteins can directly interact with Thi5 proteins (Rodriguez‐Navarro et al, ) further shows the interaction of pyridoxine and thiamine biosynthesis (Figure ).…”
Section: Vitamins That Act As Enzyme Cofactorssupporting
confidence: 78%
See 1 more Smart Citation
“…In contrast to the SNZ1/SNO1 gene pair, which is located in the middle of the right arm of CHRXIII, SNZ2 / SNO2 and SNZ3 / SNO3 are found in subtelomeric regions of CHRXIV and VI, respectively, and are flanked by the thiamine biosynthetic genes THI12 and THI5 , respectively. Their increased expression upon thiamine depletion is consistent with the role of PLP in thiamine biosynthesis (Paxhia & Downs, ). The demonstration that Snz proteins can directly interact with Thi5 proteins (Rodriguez‐Navarro et al, ) further shows the interaction of pyridoxine and thiamine biosynthesis (Figure ).…”
Section: Vitamins That Act As Enzyme Cofactorssupporting
confidence: 78%
“…Their increased expression upon thiamine depletion is consistent with the role of PLP in thiamine biosynthesis (Paxhia & Downs, 2019). The demonstration that Snz proteins can directly interact with Thi5 proteins (Rodriguez-Navarro et al, 2002) further shows the interaction of pyridoxine and thiamine biosynthesis ( Figure 1).…”
Section: Pyridoxine (B6)supporting
confidence: 70%
“…During the study of the biosynthesis, homeostasis, and metabolic network of vitamin B 6 in Escherichia coli and Salmonella enterica (16)(17)(18), we found that E. coli strains lacking pdxJ had different PL requirements than those lacking pdxH. This result was unexpected given that both lesions abolish PLP biosynthesis.…”
mentioning
confidence: 91%
“…These two enzymes, respectively, control successive catalytic steps for the synthesis of vitamin B6 (PLP) (Rodriguez-Navarro et al, 2002). SNO2(3)/SNZ2(3) are located in subtelomeric clusters together with the thiamin biosynthetic gene THI5(12), and their products physically interact in a complex that likely channels the PLP for thiamin production (Rodriguez-Navarro et al, 2002;Paxhia and Downs, 2019). In accordance with previous observations (Argueso et al, 2009;Stambuk et al, 2009), our analysis of gene CNVs revealed that all strains in the bioethanol dataset (exempting one cachaça strain) have increased copies of the SNO2(3)/SNZ2(3) region when compared with S288C.…”
Section: Genetic Signatures Of Bioethanol Yeasts and Adaptation To Industrial Fermentationmentioning
confidence: 99%